Systemic Liquidation Risk and the Diversity–Diversification Trade‐Off - WAGNER, WOLF (Journal of Finance, 2011)
ABSTRACT This paper proposes a portfolio choice model in which investors are subject to liquidation risk and (endogenously) face higher costs in the event of joint liquidation (as was observed during the crisis of 2008 to 2009). The risk of joint liquidation creates an incentive for investors to choose heterogeneous portfolios and to rationally forgo diversification benefits. Joint liquidation risk is also reflected in asset prices, resulting in (1) assets with high idiosyncratic risk having low expected returns, and (2) assets that display high correlation with the portfolios of (liquidation‐prone) investors having high expected returns.